DESA PAKRAMAN SEBAGAI LEMBAGA ADAT DAN LEMBAGA AGAMA BAGI KEHIDUPAN MASYARAKAT HINDU DI BALI - Ida Bagus Putu Eka Suadnyana (Fakultas Dharma Duta, 2020)
Desa Pakraman as a customary law community unit in Bali which has a unity of tradition and social life manners of the Hindu community has descended descendantly in the